Exploring Adolescents’ Social Media Connection and Disconnection: A Latent Class Approach - Lise-Marie Nassen; Kathrin Karsay; Laura Vandenbosch; Lara Schreurs (Media and Communication)
In industrialized societies characterized by ubiquitous connectivity, many individuals disconnect from their phones or social media to break patterns of habitual use, reduce information overload, alleviate stress, and avoid distractions. Although research has predominantly focused on (young) adults, information on digital disconnection among adolescents remains limited. In response, in the present study, we analyzed survey data from 956 Flemish adolescents in Belgium (Mage = 15.10, SD = 1.61, and 64.8% girls) and, using latent class analysis, identified two subgroups: Class 1 labeled as “low adoption of social media apps and disconnection tools,” and Class 2 labeled as “high adoption of social media apps and disconnection tools.” Adolescents in Class 2 were more likely to use social media, specifically social networking, instant messaging, and entertainment apps, and to adopt disconnection tools (e.g., iOS Screentime or the Forest app). Next, drawing on the media practice model, we investigated how sociodemographic and sociopsychological factors contribute to those usage patterns and found that girls, older adolescents, and adolescents with higher scores for depressive symptoms and flourishing were more likely to belong to Class 2. Those findings offer new insights into adolescents’ social media connection and disconnection that can inform interventions to promote healthier smartphone use among adolescents.